SCIENTIFIC AND METHODOLOGICAL FOUNDATIONS OF A SYSTEM OF SPECIAL EXERCISES FOR IMPROVING THE TECHNICAL PREPARATION OF FOOTBALL PLAYERS (World Bulletin of Physical Education and Sports Science, 2026)
This article examines the scientific and methodological foundations of a system of special exercises aimed at improving the technical preparation of football players in the context of pedagogical higher education. Technical preparation is interpreted as a multidimensional process that integrates motor coordination, precision of movement, speed of decision-making, spatial orientation, and the stable execution of game actions under variable competitive conditions. The study is based on the idea that the effectiveness of technical training depends not only on the volume of repeated actions, but also on the systematic selection of exercises corresponding to players’ age, qualification, functional readiness, and tactical tasks. The paper analyzes the pedagogical potential of special exercises directed at dribbling, passing, ball control, shooting accuracy, first touch, feints, and transition actions performed under time and space constraints. Particular attention is given to the methodological principles of progression, variability, differentiation, repetition, and game modeling in the structure of training sessions. The article also highlights the importance of combining isolated technical drills with situational and competitive exercises in order to ensure the transfer of learned skills into real match performance. It is argued that a scientifically grounded exercise system contributes to the development of technical reliability, movement economy, and adaptive motor responses. The findings support the view that special exercises should be organized as an integrated methodological complex capable of improving both individual mastery and overall training efficiency in football education.
Keywords: Football training, technical preparation, special exercises, motor coordination, ball control, passing accuracy, shooting technique, training methodology, skill development, pedagogical approach.